Code and data for the Galapagos macroplastic connectivity analysis - Ypma, Stefanie (Utrecht University, 2022)
Code and data for 'Detecting most effective cleanup locations using network theory to reduce marine plastic debris: A case study in the Galapagos Marine Reserve' by S.L. Ypma, Q. Bohte, A. Forryan, A.C. Naveira Garabato, A. Donnelly and E. van Sebille. Accepted for publication in the journal 'Ocean Science'.
Keywords: Natural Sciences - Physical sciences (1.3); Lagrangian modelling; oceanparcels; parcels; network theory; marine litter; plastic pollution; Galapagos Islands